Book Reviews / Rezensionen - Klara Zwickl; Markus Marterbauer; Eckhard Hein (Intervention. European Journal of Economics and Economic Policies, 2010)
Books reviewed: Joachim Becker, Andrea Grisold, Gertraude Mikl-Horke, Reinhard Pirker, Hermann Rauchen schwandtner, Oliver Schwank, Elisabeth Springler, Engelbert Stockhammer (2009): Hetero doxe Ökonomie, Marburg Herbert Schui (2009): Gerechtere Verteilung wagen. Mit Demokratie gegen Wirtschaftsliberalismus, Hamburg Bo Sandelin, Hans-Michael Trautwein, Richard Wundrak (2008): A Short History of Economic Thought, 2nd edition, London/New York
Keywords: 330